Study of the dynamic natural forest groups of Lebanese rice Cedrus libani A. Richard in Syria: دراسة ديناميكية المجموعات الحرجية الطبيعية للأرز اللبناني Cedrus libani A. Richard في سورية - Abeer Ahmed Ibrahim (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2017)
The aim of this study is to assess the dynamics of the forest stands of Cedrus libani A. Richard in its only natural area in Syria - Slenfeh and Jawbat Burghal. The spatial and temporal change of the natural stands of Cedrus libani during the period 1984-2011 and their health status during the period 1984-2014 were assessed using Remote Sensing and Geographic Information Systems (GIS). A high-resolution satellite image was used in 2011 and 17 Landsat images Landsat various sensors; Landsat_4, 5 and 8 and the NDVI Index were used during 1984-2014, high-resolution Google Earth (2 m). The direction and amount of the NDVI index of the Cedrus libani samples studied during the years of study were determined using ANOVA in the SPSS. The results showed a clear decrease in the Cedrus libani area size in both study sites Slenfeh and Jawbat Burghal in 2011 compared to 1984. The results also revealed a signiﬁcant increase trend of Normalized Difference Vegetation Index (NDVI) for natural stands of Cedrus libani in Slenfeh and Jawbat Burghal during 1984-2014, which reflects the good health status of the natural Cedar stands in Syria.